PENGARUH REPUTASI PERUSAHAAN, DESKRIPSI PEKERJAAN DAN E-RECRUITMENT TERHADAP MINAT MELAMAR KERJA - Rina Dewi, Putu Erika Meita; Mujiati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Intention to apply for a job is a decision made by job seekers regarding their choice of job offers and companies in the labor market. A student must have thought ahead to apply for a job, in fact they have been looking for work on the sidelines of their lectures, especially those who are already on their way to graduation. The purpose of this study is to determine the effect of company reputation, job description, and e-recruitment on intention to apply a job at the Faculty of Economics and Business, Udayana University. The population in this study amounted to 599 students, and the sample amounted to 240 students. The sampling method used is proportionate random sampling. Data was collected using a survey approach, where the research instrument used was a questionnaire. The analysis technique used in this research is multiple linear regression analysis. The results showed that there was a positive and significant influence between company reputation on intention to apply a job, there was a positive and significant effect between job descriptions on intention to apply a job, there was a positive and significant effect between e-recruitment intention to apply a job on the student at the Faculty of Economics and Business, University Udayana.